The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1074/jbc.m114.603043
|View full text |Cite|
|
Sign up to set email alerts
|

Zinc-binding Domain-dependent, Deaminase-independent Actions of Apolipoprotein B mRNA-editing Enzyme, Catalytic Polypeptide 2 (Apobec2), Mediate Its Effect on Zebrafish Retina Regeneration

Abstract: Background:The mechanism by which Apobec2 stimulates retina regeneration remains unresolved. Results: Apobec2 lacks cytosine deaminase activity and interacts with proteins that regulate retina regeneration. Conclusion: Apobec2 subcellular localization is regulated by sumoylation and requires a zinc binding domain and protein interactions to regulate retina regeneration. Significance: This study delineates previously unidentified biochemical functions of Apobec2 proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…Interestingly, Zhou et al [31] demonstrated that Pou6f2 i s present in the developing and adult retinal ganglion cells. This gene product is also associated with the regeneration of neurons in zebrafish [57].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Zhou et al [31] demonstrated that Pou6f2 i s present in the developing and adult retinal ganglion cells. This gene product is also associated with the regeneration of neurons in zebrafish [57].…”
Section: Discussionmentioning
confidence: 99%
“…Apobec2 has been implicated in DNA demethylation (18), a process essential for normal myoblast differentiation and fusion into myotubes (50), as well as for normal development in zebrafish and Xenopus (1417). Our results confirmed the localization of mouse Apobec2 in the sarcomeric Z-lines in adult muscle tissue and in primary cultured myotubes, as has been reported for zebrafish Apob2b (13).…”
Section: Discussionmentioning
confidence: 99%
“…Muscle defects associated with Apobec2 deficiency have been also documented in zebrafish by using morpholino oligonucleotide–mediated knockdown of the Apobec2 proteins (Apo2a and Apo2b), which demonstrated myopathy in the somitic musculature (evidenced by the presence of cell-free spaces, long myofibers, and impaired heart function) (13). Recent studies have suggested that Apobec2 might also play important roles in the regulation of left-right axis specification in Xenopus (14) and retinal regeneration of zebrafish glial cells (1517). The exact molecular mechanism of Apobec2 action remains unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on its homology with the other AID/APOBEC family members, it has been hypothesized that APOBEC2 may be involved in RNA editing (W. Liao et al, 1999;Okuyama et al, 2012) or DNA demethylation (Guo et al, 2011;Powell et al, 2012;Rai et al, 2008). It has also been hypothesized that it has lost its deaminase activity altogether and may act biologically by a novel mechanism (Powell et al, 2014). However, there is currently a lack of knowledge on the direct physiological targets of APOBEC2, and its mechanism of action.…”
Section: Introductionmentioning
confidence: 99%